(untitled) (Revista de Ensino em Artes, Moda e Design, 2026)
The absence of technical documentation and laboratory testing on textile materials with potential for application in clothing products remains a challenge for the apparel industry. In this context, this article aimed to develop two textile swatches based on the technical analysis of knit fabrics collected from the industry in Cianorte (PR), contributing to the physical and digital collection of the Tecidoteca Extension Project. The knit samples — one circular (single jersey) and one flat (rib knit) — were subjected to standardized tests (ABNT and ISO), assessing density, fabric weight, shrinkage, pilling, sensory hand feel, elongation, and elasticity. The results indicated significant structural differences between the knits: the rib knit exhibited greater elasticity (95.23%) and resistance to pilling (grade 5), while the single jersey showed lower performance (36.61% and grade 2, respectively). The research reinforces the integration of teaching, research, and extension, valuing textile knowledge and strengthening the critical and applied training of future fashion professionals.